ANALISIS PENDAPATAN USAHATANI LAHAN KERING DALAM HUBUNGAN DENGAN KONSERVASI TANAH DAN AIR (Income Analysis of Dry Land Farming in Relation With Soil and Water Conservation) - Nimrot Neonufa (Politeknik Pertanian Negeri Kupang, 2016)
The impacts of population density are the decrease of land produktivity, land availibility, and the decrease of food crops supply. Therefore, the development of conservation based farming is necesary to beÂ done in dry land area in order to fulfill horizontal demand between timber and food conducted in Naioni Vilage, Kupang District by the use of interview method. Linear correlation analisys, multiple linear regression analisys, rank Spearman analisys and R/C ratio analisys were employed in this research. In showed, only age as socio-economics factor individually, had significant (R2) 40,5%. The width of farm-land used had signivicant relation to the cost of soil and water conservation per family per year. This phenomenon indicated that farmer with small farm-land had the sense of care and more rensponse to the issue of soil and water conservation. Ratio between farming income and the cost of soil and water conservation was more than one (R/C >1), means economically, soil and water conservation farming is efficient.Key words : Farming, dry-land, soil and water conservation, R/C ratio analysis, revenue.